Readings of Plato's Apology of Socrates defending the philosophical life - Haraldsen, Vivil Valvik (Lexington Books, 2018)
Contributors to this volume focus on the character of Socrates as the embodiment of philosophy, employing this as a starting point for exploring various themes exposed in the Apology. These include the relation of philosophy to democracy, rhetoric, politics, or society in general, and the overarching question of what comprises the philosophic life.